Supply chain vulnerabilities impacting commercial aviation - Koepsel, Kirsten M., 1953- $eauthor (Society of Automotive Engineers, 2019)
This book addresses the big question facing aircraft manufacturers today: keep the work in house or outsource it? The ongoing battle between cost cutting and supply-chain control is ever more visible as aircraft OEMs have full order books and tight delivery schedules. Since the 1980s, commercial aviation, like many other industries, looked for ways of more economically sourcing parts and services. The new partnerships between OEMs and suppliers at multiple levels, did make the industry nimbler and more flexible. Yet, it also introduced a higher level of instability, risks and vulnerabilities to the aviation ecosystem.
Keywords: Aeronautics, Commercial -- Materials management.; Business logistics.; elektronické knihy; electronic books